Can case-based learning-oriented science teaching materials improve critical thinking skills? - Fembriani, Fembriani; Siswandari, Siswandari; Joyoatmojo, Soetarno; Efendi, Agus (Edelweiss Applied Science and Technology, 2025)
Case-based learning-oriented science teaching materials are increasingly recognized as essential tools to enhance students' critical thinking skills. This study examines the feasibility and effectiveness of science teaching materials developed using a case-based learning (CBL) approach. This research employed a research and development (R&D) design based on the Borg and Gall model. The sample was selected randomly from 66 undergraduate students from the Primary School Teacher Education Program at Nusa Cendana University, Indonesia. Data analysis techniques included descriptive statistics, feasibility analysis based on expert judgment using a set of criteria scores, and critical thinking test results analyzed using t-tests and normalized gain (N-gain) scores. The results indicated that: (1) The CBL-based science teaching materials were considered highly feasible for use in the Elementary Science Concepts course, as evidenced by expert validation scores: linguistic expert (82.7%), subject matter expert (84.2%), instructional design expert (84.0%), and practitioner (86.4%), all of which fall into the "outstanding" category. (2) The materials were also found to be effective in enhancing students' critical thinking skills, with a significance value of 0.000 < 0.005 and an N-gain score of 0.645, which is categorized as moderate improvement.